2018
DOI: 10.1159/000491538
|View full text |Cite
|
Sign up to set email alerts
|

Klf4 Alleviates Lipopolysaccharide-Induced Inflammation by Inducing Expression of MCP-1 Induced Protein 1 to Deubiquitinate TRAF6

Abstract: Background/Aims: Inflammation is an essential component of innate immunity against pathogens, but is tightly regulated, such as by Krüppel-like factor 4 (Klf4), to prevent injury. Klf4 also regulates macrophage polarization, although the mechanisms underlying both functions are poorly understood. The aim of this study was to investigate whether and how Klf4 prevents unregulated inflammation. Methods: The bone marrow-derived macrophages and RAW264.7 cell line were used. Quantitative real-time PCR was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Acting as a deubiquitinating enzyme, MCPIP1 inhibits NF-κB and c-Jun N-terminal kinase (JNK) signaling pathways by removing the ubiquitin moieties from TNF receptor-associated factors (TRAFs), including TRAF2, TRAF3 and TRAF6 [150].As an RNase, MCPIP also regulates inflammatory cytokines like IL-6 by regulating RNA decay [151] and innate defense via degrading viral RNA [152]. MCPIP deubiquitinates TRAF6 to impede NF-κB signaling [89].…”
Section: Other Dubsmentioning
confidence: 99%
“…Acting as a deubiquitinating enzyme, MCPIP1 inhibits NF-κB and c-Jun N-terminal kinase (JNK) signaling pathways by removing the ubiquitin moieties from TNF receptor-associated factors (TRAFs), including TRAF2, TRAF3 and TRAF6 [150].As an RNase, MCPIP also regulates inflammatory cytokines like IL-6 by regulating RNA decay [151] and innate defense via degrading viral RNA [152]. MCPIP deubiquitinates TRAF6 to impede NF-κB signaling [89].…”
Section: Other Dubsmentioning
confidence: 99%
“…Studies showed that the TLR4-NF-jB signalling pathway plays a key role in the production of inflammatory cytokines. [4][5][6] To investigate the regulatory mechanisms by which SNG inhibits LPS-induced inflammatory cytokine production in HK-2 cells, we incubated HK-2 cells in medium with different concentrations of SNG in vitro and then used LPS to induce cells to produce inflammatory cytokines. We detected the expression levels of TLR4-NF-jBassociated protein by Western blotting.…”
Section: S-nitrosoglutathione Inhibited Toll-like Receptor 4-nuclear mentioning
confidence: 99%
“…Previous studies reported that the incidence of septic AKI is 30–50% in the intensive care unit (ICU), and resulting in a mortality rate of 35–60% . The endotoxin produced by Gram‐negative bacteria is the main trigger for inflammatory response to sepsis, and lipopolysaccharide (LPS) as one of the major outer membrane components of Gram‐negative bacteria is the most important factor in the induction of septic AKI …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the protein was also found to be a part of the deubiquitinase complex that facilitates the deubiquitination of tumour necrosis factor receptor-associated factor (TRAF) proteins. Deubiquitinase-associated activity of MCPIP1 leads to inhibition of nuclear factor kappa B (NFκB) signalling in immune cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%